From Franco´s propaganda to the Brand Spain: 70 years of Spanish Foreign Radio. - Ortiz Sobrino, Miguel Ángel (Historia y Comunicación Social, 2014)
In 2012, it was the LXX anniversary of the international emissions of the Spanish National Radio that, since 1977, have been issued under the name Spanish Foreign Radio. Although they started as an advertising instrument of the Franco dictatorship, the establishment of a Parliamentary Monarchy after Franco ´s dead, in 1975, supposed a change in the station. Right then, their emissions have served to export to the world the new democratic standards and values of Spain as a country.